Adults' Exposure to Unhealthy Food and Beverage Marketing: A Multi-Country Study in Australia, Canada, Mexico, the United Kingdom, and the United States. (11th May 2022) - Nieto, Claudia; Jáuregui, Alejandra; Contreras-Manzano, Alejandra; Potvin Kent, Monique; Sacks, Gary; White, Christine M; Pauzé, Elise; Vanderlee, Lana; Thrasher, James F; Barquera, Simón; Hammond, David
ABSTRACT: Background: Food marketing increases product appeal, purchasing, and consumption, using diverse strategies and locations to reach consumers. Objectives: The aim of this study was to examine differences in adults' self-reported exposure to various marketing strategies (brand and licensed characters, celebrities, and sponsorship of sports and cultural events) and locations (television, radio, and digital media) across 5 countries: Australia, Canada, Mexico, the United Kingdom, and the United States. Methods: We analyzed cross-sectional survey data on self-reported exposure to food marketing strategies and locations collected in 2018 by the International Food Policy Study. Participants ( n = 21, 678) aged ≥18 years completed an online survey. Exposures to unhealthy food marketing strategies and locations in the prior 30 days were self-reported. Regression models examined differences in marketing exposure and locations across countries. Results: The average number of unhealthy food marketing strategies to which participants reported being exposed ranged from 0.5 in the United Kingdom to 2.3 in Mexico. Self-reported exposure to strategies across all countries was highest for brand characters (32%), followed by licensed characters (22%). In total, the reported mean exposure of marketing locations was 1.6 in the prior month. Television was the most prevalent location (44%), followed by digital marketing (32%). Adjusted models indicated that the odds of reporting exposure to marketing strategies and marketing locations were higher for Mexico compared to the rest of the countries. Conclusions: Adults report a variety of exposures to unhealthy food marketing in all countries, but exposure was highest in Mexico. Special attention should be paid to regulating marketing strategies, such as brand characters and licensed characters, and locations, such as television and digital marketing.